STRATEGI LAPORAN KEUANGAN UMKM TANGERANG SELATAN MELALUI SI-APIK - Aris Sanulika; Wahyu Nurul Hidayati; Tri Agung Tofiq; Ambarwati Ambarwati (PENGABDIAN SOSIAL, 2021)
ABSTRACT The community service activity aims to assist UMKM in overcoming problems with recording financial statements. As for the form of activities in the implementation of community service with the theme of financial accounting. The results of the PKM implementation were to add to their knowledge in the field of accounting and financial statement. South Tangerang UMKM participants were very enthusiastic about the material they got from Pamulang University accounting lecturers. Participants could immediately practice bookkeeping through the SI-APIK application. The response of the participants was very good and happy because it was greatly helped in learning about financial recording. The importance of managing the financial aspects of the business makes UMKM aware that income must be rotated so that the business continues. PKM activities should be encouraged and made as attractive as possible in order to attract more UMKM participants in South Tangerang, to expand the coverage of the material area so that participants can gain more insight. Keywords: Financial Statement, SI-APIK, UMKM. ABSTRAK Tujuan kegiatan pengabdian kepada masyarakat ini adalah membantu UMKM dalam mengatasi persoalan-persoalan pencatatan laporan keuangan. Adapun bentuk kegiatan dalam pelaksanaan pengabdian kepada masyarakat dengan tema akuntansi keuangan. Hasil pelaksanaan PKM adalah menambah ilmu mereka di bidang akuntansi, pencatatan keuangan.Para peserta UMKM Tangerang Selatan yang sangat antusias dengan materi yang mereka dapatkan dari dosen-dosen akuntansi Universitas Pamulang, Para peserta dapat langsung mempraktekan pembukuan melaui aplikasi SI-APIK. Respon para peserta sangat baik dan senang karena sangat terbantu dalam pembelajaran tentang pencatatan keuangan. Pentingnya pengelolaan aspek keuangan usaha membuat para UMKM sadar bahwa pendapatan harus di putar agar usaha terus maju. Kegiatan PKM kedepannya agar digalakan dan dibuat semenarik mungkin agar dapat menjaring lebih banyak lagi peserta UMKM di Tangerang Selatan, perluasan jangkauan cakupan wilayah materi bisa lebih diperluas sehingga peserta dapat memperoleh wawasan lebih banyak. Kata Kunci: Laporan Keuangan, SI-APIK, UMKM.